Long survival and recurrence of thymic carcinoma 10 years after resection. (June 2019) - Yabuki, Hiroshi; Minowa, Muneo
Thymic carcinomas are a rare type of malignant mediastinal tumor. Thymic carcinomas have a rapid progression, and recurrence and metastasis usually occur in the early phase after surgical resection. To the best of our knowledge, recurrence more than 10 years after surgical resection has been reported in only one case of neuroendocrine cell carcinoma. We report a case of resected thymic squamous cell carcinoma recurring after 10 years, which indicates that thymic carcinomas require long-term follow-up after surgical resection.